Maximizing Mudharabah Savings and Mudharabah Deposits against Mudharabah Financing Sharia of Commercial Bank - Prianda Pebri; Surya Bakti (Budapest International Research and Critics University, 2021)
The purpose of this study is to partially and simultaneously determine the effect of mudharabah savings and mudharabah deposits on mudharabah financing at Commercial Sharia Bank. It is quantitative reserach. The population in this study is the Statistics of Sharia Banks (SPS), which includes statistics on mudharabah savings, mudharabah deposits, and mudharabah financing for Sharia Commercial Banks from January 2015 to December 2019 which comes from the Statistics of Sharia Banks (SPS). This data is obtained from Financial Services Authority website with link www.ojk.go.id. which is published monthly. Data analysis is using multiple linear regression analysis. The results show as partially, it is only mudharabah savings have a positive and significant effect on mudharabah financing for Sharia Commercial Banks. While mudharabah deposits have no effect on the mudharabah financing of Sharia Commercial Banks. Furthermore, simultaneously the two independent variables, which are mudharabah savings and mudharabah deposits have a positive and significant effect on mudharabah financing for Sharia Commercial Banks.